Kegiatan Pembinaan dan Pengembangan Minat Baca (Pelatihan Menulis) Bagi Guru-Guru SMP Se-Kota Medan - Gemala Widiyarti; Kevin Ateta Sitepu; Anggi Pebrina Peranginangin (Universitas Islam Negeri Sumatera Utara, 2023)
AbstractThe participants in this activity were Middle School teachers throughout Medan City. This activity was attended by four hundred participants. The hope of this activity is that writing literacy can develop among teachers and can be passed on to students. The world of Literacy continues to grow, the public's interest in participating in encouraging literacy is also starting to sprout. Not only the growth of interest in reading but this enthusiasm is also seen in the world of writing. The ease with which reading material is obtained through online media inspires them to write as well. Writing platforms grow like mushrooms in the rainy season. This causes the writing culture to suddenly become very popular. Social media such as Facebook, Instagram, WhatsApp or other platforms that have monetary value are places where they share their ideas and feelings. Some have even recorded works from these uploads. Novels, collections of short stories, travel, culinary, or other themes become material that can be recorded. They have done, the profession of a writer also carried. At this level it is necessary to continue to hone skills. So that the writing does not just appear, but there is a quality that accompanies it. Both in terms of grammar and from the content of writing. For this reason, efforts are needed to improve this ability. So, in this case we as the Pasuruan Book Writing Community intend to hold training to improve the ability of writers in terms of quality. In collaboration with the Association of Educators and Writers of North Sumatra, the Medan City Library and Archives Service carried out an activity to Develop Interest in Reading Through Writing which became